KOMPARASI PENILAIAN EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER PADA LPD PECATU DAN MENGWI - Kusuma, I Putu Angga; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
This research is a comparative study to find differences in the effectiveness of computer-based accounting information systems on LPD Indigenous Village Mengwi with LPD Desa Adat Pecatu. Variables used to compare the efficacy is eight variables: data security, time, accuracy, variation of the report, relevance, physical comfort, economy and satisfaction pengguna.Metode Data collection is questionnaires and interviews with LPD employee who works in Indigenous Village Mengwi and Pecatu. The population in this study were all employees and employee at Desa Adat LPD Mengwi and Pecatu. The samples used by 74 employees and an employee is working on a computer and is associated with the use of computer accounting information systems, with a purposive sampling method. The analysis technique is the t-test 2 samples. Based on the results there are differences in the effectiveness of the application of computer-based accounting information systems on LPD Indigenous Village Mengwi with Pecatu.
Keywords: Comparative, Effectiveness, Accounting Information Systems.